TRANSCENDING BOUNDARIES – REPRESENTATION OF CHANGING GENDER DYNAMICS IN SELECT INDIAN TELEVISION ADVERTISEMENTS - Joseph, Solomon Asha; Mathew, Leena Liz; D. R., Fancy; S., Saran (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Advertisements are primarily intended to persuade the consumers to buy a particular brand of product. In modern times Television advertisements or TV commercials as they are known, have emerged as one of the most visible and popular form of advertisements. Traditionally, selling a product entailed roping in a celebrity to either pose with the product or to highlight its advantages over other products. But the advent of various domestic and foreign channels offered the viewers the option to skip the advertisements and switch over to more interesting content in other channels. Besides, the stiff competition between the brands necessitated the advertisements to be more creative, resulting in the incorporation of engaging storylines. Thus, advertisements have transitioned from a means for merely selling products to cultural artefacts mirroring the socio-cultural practices and values of the society. They portray social norms, cultural reality, and gender patterns in keeping with the patriarchal ideology. Culture profoundly impacts gender-related behavior, roles, values, identity, and their perception in various social contexts. It governs the expectations placed on men and women and influences their attitudes and behavior. Since advertisements are predominantly created by men with the intention of appeasing the male consumers, women are often objectified. The recent decades have seen women progress in leaps and bounds but the advertisements have been slow in acknowledging their achievements. The winds of change have been very subtle but steady progress is being made in making progressive and socially relevant ads which has captured man - woman equation from a different angle. This paper proposes to analyze select TV advertisements that appeared after 2000 which show both men and women breaking away from the narrow confines of patriarchy to don new and unconventional roles.